Crystal structure of 5′-(9-phenyl-9H-carbazol-3-yl)-[2,2′-bithiophene]-5-carbaldehyde, C27H17NOS2 - Zhao Wen-Ze; Lu Feng-Jun (Zeitschrift für Kristallographie - New Crystal Structures)
C27H17NOS2, monoclinic, P21/c (no. 14), a = 17.5582(11) Å, b = 12.4355(8) Å, c = 10.0535(5) Å, β = 103.391(2)°, V = 2135.5 Å3, Z = 4, Rgt(F) = 0.0555, wRref(F2) = 0.1093, T = 273 K.